Impact Of Zootechnical Parameters On Cell Quality Of Cattle Milk (semi-arid Costal Tunisia) - Haj Mbarek, R.; M’sadak, Y. (University of Eloued جامعة الوادي, 2015)
The work was realized on a sample of 50 cattle herds, conducted in aboveground, in a coastal area of the semi-arid Tunisia, by using investigation related to cows and their breeding and milking conditions as well as despoliation in milk control data. Analysis of the data relating to the parameters of udder conformation and cow cleanliness revealed that “Udder depth” settings “Udder cleanliness” have been shown to affect the ICC and are considered factors risk of bovine mastitis. The study of breeding and milking conditions highlight some significant factors on changes on the variation of cell counts and the probability of the spread of mastitis, especially the "No disinfection of teat." The level of housing, the analysis revealed that the use of a litter reduced to half the average of ICC which proved highly related to the cleanliness of both the sleeping area as the udder.
Articale in Journal of fundamental and Applied Sciences Vol. 07, N. 03
Keywords: Cell counts; Udder conformation; Clean cows; Breeding and milking conditions; Semi-arid Tunisia.